Nocardia rubra cell-wall skeleton activates an immune response in cervical tissue via stimulating FPR3 to enhance dendritic cell-mediated Th1 differentiation - Guo, Qianyu; Chen, Wei; Sun, Junyi; Zhao, Chunfang; Bai, Xue; Zhang, Yanan; Liu, Ke; Zhang, Lei; Shao, Suxia (Frontiers in Immunology, 2023)
Nocardia rubra Cell Wall Skeleton (Nr-CWS) has proven to be a successful medicine for cervical HPV infection therapy. This might be due to its stimulatory effect on the host immune system, while the mechanisms are not well characterized. We previously found that CD4+ T cells were increased in cervical tissue after Nr-CWS treatment. Microarray data gained with these cervical tissues showed that the expression of formylated peptide receptor 3 (FPR3) was significantly upregulated. This study aimed to explore the role of Nr-CWS in immunomodulatory based on these findings. In cervical tissue from patients who received Nr-CWS, we examined CD4+ T cell subsets and discovered a substantial rise in Th1 cytokines and transcription factors. The regulatory effects of Nr-CWS on the function and phenotype of dendritic cells (DCs) were assessed in comparison with the traditional DC maturation inducer LPS. Similar to LPS, Nr-CWS potently induced DC maturation and IL-12 secretion. Furthermore, the differentiation of T cells induced by Nr-CWS stimulated DCs, as assessed using Mixed Lymphocyte Reaction (MLR) assays, was significantly towards Th1. Finally, we measured FPR3 expression in DCs in response to Nr-CWS and LPS. Interestingly, Nr-CWS potently upregulated FPR3 expression, while the LPS did not. Silencing FPR3 in DCs reduced Nr-CWS-induced IL-12 production and Th1 cell polarization in co-cultured T cells. In conclusion, Nr-CWS may target FPR3 on the surface of DC cells and activates a Th1-type immune response, representing its basis for antiviral immune effects on HPV.